Gender-Specific Differences in Corporal Punishment and Children’s Perceptions of Their Mothers’ and Fathers’ Parenting - Mehlhausen-Hassoen, David (Journal of interpersonal violence, 2021)
Corporal punishment is a widespread phenomenon and a common malformation of parenting. Gender is a core category of social order and family structure. Gender-specific differences in parenting and violent behavior have been studied for many years. Yet, relatively little is known about the impact of gender interactions on parent-to-child physical violence or the impact of such violence on children’s perceptions of their parents’ behavior. This study used data collected from 618 students in academic institutions in northern Israel to examine the relationship between different gender interactions (e.g., mother–daughter, mother–son, father–daughter, and father–son) and the frequency of corporal punishment experienced by the respondents when they were in elementary school (between the ages 6 and 12). This study also examined whether gender interactions influence the relationship between corporal punishment and respondents’ perceptions of their parents’ behavior, namely the perceived parenting the respondents received during childhood. Cross tabulations and repeated measures were used to analyze the data. Significantly fewer daughters (as compared with sons) experienced corporal punishment and significantly fewer daughters experienced corporal punishment from both parents. Corporal punishment had a significant negative impact on the perceived parent–child relationship. Violent parental behavior had a significantly stronger effect on the perception of the father–child relationship, as compared with the perception of the mother–child relationship, even when the mother was the violent parent. These findings point to the importance of gender interactions in research and psychosocial practice.